Heavy Metal Contamination of Paediatric Paracetamol and Ascorbic Acid Drug Products in South-West Nigeria. (2019)
Background: Water is a primary contributor to human populations’ heavy metals exposure and industrial contamination of products. Consequently, paediatric medications because of their high-water constitution can contribute significantly to intake of heavy metals in excess of allowable limits. There is therefore a need for effective preventive and control strategies. Unfortunately, studies investigating heavy metal content in paediatric formulations in Nigeria are scarce and often limited in the range of elements assayed. Objective: To evaluate elemental impurities in the two most frequently administered paediatric medications-paracetamol and ascorbic acid marketed in South-west Nigeria. Methods: Thirteen paediatric syrup brands were used for the study. Sample pretreatment involved dry ashing followed by digestion using concentrated aqua regia (nitric acid:hydrochloric acid, 3:1). Chromium, lead, copper, cadmium, zinc, nickel, cobalt and manganese were assayed with the atomic absorption spectrophotometer with the limit of detection set at 0.001. Results: The most abundant metal ions present in all the formulations were chromium (1.16-1290.2 mg/) and nickel (2.37-1289.0 mg/L). Cadmium was detected at low concentration in only two of the brands while lead was detected in three brands at concentrations ranging from 0.09 - 0.12 mg/L. The calculated expected daily exposures of lead in the three brands were in excess of the permissible daily exposure for oral drug products. Conclusion: Some of the paracetamol and vitamin C syrups sold in the South-West of Nigeria are contaminated with cadmium, nickel and lead.